1980
DOI: 10.1007/bf02395308
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA integrity and rate of seed germination

Abstract: The integrity of ribosomal RNA (the percentage of complete, un-nicked molecules) in seeds was studied by electrophoresis under denaturing conditions. Two batches of carrot seed, harvested at different stages of maturity, and four batches ofNicotiana seed stored for various times were used. Within each species, there was a correlation between the integrity of the rRNA of the dry seed and the rate of germination of that seed. In carrot seed, there was extensive degradation of existing rRNA in both the embryo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 8 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…These results suggest that the rRNAs undergo some degradation in the seed when in the dry state or during dessication. Similar results were reported for carrot and tobacco (Brocklehurst and Fraser 1980). However, as most of the preformed ribosomes are still able to function in protein synthesis, the structure of the rRNAs is probably not too affected by this degradation.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that the rRNAs undergo some degradation in the seed when in the dry state or during dessication. Similar results were reported for carrot and tobacco (Brocklehurst and Fraser 1980). However, as most of the preformed ribosomes are still able to function in protein synthesis, the structure of the rRNAs is probably not too affected by this degradation.…”
Section: Discussionsupporting
confidence: 88%
“…d Semi-quantitative analysis by image analysis of 28S and 18S rRNAs (black and grey bars, respectively; means ± SE; n = 5 biological replicates of 20 ground seeds). Circles denote total germination as in b. Asterisks in b and d indicate differences between non-aged control seeds and Aged or dead seeds at a level of P \ 0.01 (one-way ANOVA) (Bray and Chow 1976;Boubriak et al 2000;Brockelhurst and Fraser 1980;Cheah and Osborne 1978;Osborne 2000). The final, or execution, phase of PCD is characterised by inter-nucelosomal DNA fragmentation (Elbaz et al 2002;Hengartner 2000;Thomas and Franklin-Tong 2004) and can include RNA degradation (Hoat et al 2006;Perrin et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…It is therefore surprising that the integrity of nucleic acids during seed ageing has received relatively little attention in the recent literature. Changes in nucleic acid content (Brockelhurst and Fraser 1980;Osborne 1974, 1977;Thompson et al 1987) and more recently, DNA fragmentation Osborne 2000), have been reported in seeds in relation to maturation and germination rate. Single and double strand breaks of DNA accumulate in ageing seeds (Tuteja et al 2001) and DNA fragmentation was correlated with seed death induced by drying in 'recalcitrant', i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of rRNA in aged seeds has been long studied [57][58][59][60][61] and RNA integrity number (RIN) was proposed to measure RNA quality [62,63]. Recently, Fleming and her colleagues applied RIN to assess seed aging status [29,30] and showed that RNA integrity decreased during seed aging in several plant species.…”
Section: The β Value Can Be Used To Describe the Rate Of Mrna Degradamentioning
confidence: 99%